Increased dietary 5-hydroxytryptophan reduces fearfulness in red junglefowl hens (Gallus gallus) - Lundgren, Kristoffer Anton; Løvlie, Hanne (Frontiers in Physiology, 2023)
Our production animals typically suffer poor welfare, which can be revealed by measuring the affective state these animals are in. Negative affective state is linked to poorer welfare, and can be measured as fearfulness. While continuing to research how to improve animal welfare, a compliment to reduce negative affective state could therefore be to reduce individuals' fearfulness, similar to how negative affective states are medicated in humans. A proposed mechanism for this is via the monoaminergic systems. This is based on previous studies across species that have linked the serotonergic system and fear-related behaviour. We here aimed to experimentally manipulate the serotonergic system in red junglefowl hens (Gallus gallus), the main ancestor of all domesticated chickens. We measured fearfulness as latency remaining immobile in a tonic immobility test, and did so both before and after our experimental manipulation. We set out to experimentally manipulate the serotonergic system via sub-chronic dietary treatment of 5-hydroxytryptophan (the precursor to serotonin). Our dietary manipulation of 5-hydroxytryptophan significantly reduced measured fearfulness in the manipulated hens, while latency in tonic immobility did not significantly change in our unmanipulated, control hens. This finding is promising since it indicates that increased tryptophan levels can be used to reduce fearfulness. Additionally, our result suggests that this can be done non-invasively via food (instead of injections), thus presenting a potentially feasible manipulation also for larger settings. Nevertheless, the serotonergic system is complex and its role in modulating behaviour in the fowl should be explored further to evaluate our findings, and more directly explored also in a production setting.